Influence of mixtures of acenaphthylene and benzo[a]anthracene on their degradation by Pleurotus ostreatus in sandy soil - Rocha, Inês (2021)
Polycyclic aromatic hydrocarbons (PAHs) are a class of organic compounds commonly found as soil contaminants. Fungal degradation is considered as an environmentally friendly and cost-effective approach to remove PAHs from soil. Acenaphthylene (Ace) and Benzo[a]anthracene (BaA) are two PAHs that can coexist in soils; however, the influence of the presence of each other on their biodegradation has not been studied. The biodegradation of Ace and BaA, alone and in mixtures, by the white rot fungus Pleurotus ostreatus was studied in a sandy soil.